A Survey on Investigating Data-Sharing Behavior among STEM Researchers: The Context of a Developing Country - Wilda Syahri; Yusnaidar Yusnaidar; Muhaimin Muhaimin (Indonesian Research Journal in Education |IRJE|, 2021)
Based on an extended theory of planned behavior (TPB), this study focused on five exogenous constructs (perceived benefits, facilitating condition, normative belief, behavioral belief, and control belief) that was established to predict behavioral intention and behavior of data-sharing. The research model was tested with 157 Indonesian researchers from science, technology, engineering, and mathematics (STEM). We applied the partial least squares (PLS) techniques to analyze the data. Seven out of eleven hypotheses are supported based on the significance test in through the PLS-SEM procedure. The study’s findings show that the proposed extended TPB is a valid and reliable framework for describing the data-sharing behavior of STEM researchers. This paper facilitates an advanced investigation through PLS-SEM approaches toward behavioral intention and behavior regarding data-sharing; the findings are among the first elaborated data-sharing report in the Indonesian context, a country with more than 200 thousand researchers.